Preparation method and application of sulfonated transition metal coordinated natural polymer material retanning agent
By combining collagen with transition metals, the sulfonated transition metal coordination natural polymer material retanning agent is prepared, which solves the pollution problem in the treatment of tanning blue leather chips, and achieves efficient recycling of materials and improves performance.
Patent Information
- Application Number
- CN202211233051.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-10
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2042-10-10
AI Technical Summary
The incineration and disposal methods of tanne blue leather chips and direct landfills have problems such as water pollution, land pollution, and air pollution, and have failed to effectively recycle the parts that are useful to tannery.
By combining collagen in blue leather chips with transition metals, a sulfonated transition metal coordination natural polymer material retanning agent is prepared, which is used in the retanning process in the tanning industry to improve the water solubility and tanning performance of the material.
It has achieved the reduction of solid waste emissions, reduced pollution, and improved the performance and recycling rate of leather materials.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of leather making, in particular to a preparation method and application of a sulfonated transition metal coordinated natural polymer material retanning agent. Background Art
[0002] Tannery blue leather shavings are classified as hazardous solid waste because they contain chromium. Their disposal is typically by incineration, removing organic matter and water from the system, leaving a powder of residual inorganic salts and chromium. This powder is then landfilled. This method reduces the volume and weight of the shavings by approximately 90%, while also minimizing potential water and land pollution during transportation and landfill. However, during incineration, chromium easily oxidizes to hexavalent chromium, forming fly ash that contributes to air pollution. Alternatively, the shavings can be directly landfilled, but this shifts the disposal of solid waste to the next generation and is not the most desirable method.
[0003] With the growing popularity of environmental concepts such as carbon neutrality and carbon recycling, there is a growing desire for closed-loop recycling of hazardous waste. Therefore, extracting the useful fraction of blue leather shavings from tanneries and reusing it in the leather industry can reduce solid waste emissions. Blue leather shavings primarily consist of approximately 55% water, 40% organic matter, and 5% inorganic salts. The organic matter primarily consists of collagen, a natural polymer containing carboxyl and amino groups. Therefore, using collagen as an organic ligand, combined with transition metals, to prepare transition metal-coordinated polymer materials specifically for leather production is feasible. Summary of the Invention
[0004] The invention provides a sulfonated transition metal coordinated natural polymer material retanning agent, which solves the problems of water pollution, land pollution, air pollution and the like caused by incineration of tannery blue leather scraps and landfilling. The invention realizes the extraction of the part of the tannery blue leather scraps that is useful to the tannery and reuses it in the leather industry, thereby achieving the purpose of reducing the discharge of solid waste.
[0005] The present invention adopts the following technical solutions:
[0006] A method for preparing a sulfonated transition metal coordinated natural polymer material retanning agent comprises the following steps:
[0007] Step 1: Take 100 parts of blue leather scraps, add 500 parts of deionized water, mix well, add 8-12 parts of alkali, react at 60-90°C for 3-6 hours, cool to room temperature, add 5-10 parts of calcium hydroxide, 1 part of polyaluminum chloride, and 1 part of polyacrylamide to flocculate and precipitate, filter the precipitate, take the filtrate, add sulfuric acid to adjust the pH to 7-8, and vacuum dry to obtain collagen powder;
[0008] Step 2: 100-150 parts of ferric chloride, 25-50 parts of aluminum chloride, 0-25 parts of cobalt chloride, 10-15 parts of mellitic acid, 30-50 parts of terephthalic acid, 60-80 parts of trimesic acid, 15-30 parts of collagen powder, and 35-60 parts of N,N-dimethylformamide are mixed in a hydrothermal reactor, heated to 130-160° C. within 1 hour and kept at a constant temperature for 18-24 hours. After cooling to room temperature, 100-120 parts of N,N-dimethylformamide are added and stirred for 30 minutes. The mixed solution is filtered and washed with N,N-dimethylformamide. The filter residue is transferred into 200 parts of N,N-dimethylformamide and stirred at room temperature for 24 hours. The mixture is then filtered again, washed with ethanol, and the filter residue is transferred into 200 parts of ethanol and stirred at room temperature for 24 hours. After filtering, vacuum drying is performed to obtain a transition metal coordinated natural polymer material powder;
[0009] Step 3: Take 100 parts of transition metal coordinated natural polymer powder and 5-15 parts of sodium metabisulfite and dissolve them in 200-300 parts of water, mix them evenly, react at 80-100° C. for 3 hours, and then vacuum dry the product to obtain a sulfonated transition metal coordinated polymer material retanning agent.
[0010] In a further improvement, the alkali is sodium hydroxide, potassium hydroxide or calcium hydroxide.
[0011] An application of a sulfonated transition metal coordinated natural polymer material retanning agent, comprising at least a retanning step;
[0012] The specific steps of the retanning process are: based on the weight of the wet blue leather, controlling the drum temperature at 30-35 DEG C, adding 50-100% of water, adding 2-4% of an acid-resistant fatliquor and 0-2% of fatty aldehyde, rotating for 20 minutes, adding 1-3% of chromium powder and 4-8% of a sulfonated transition metal coordinated natural polymer material retanning agent, rotating for 60 minutes, then adding 1% of sodium formate, rotating for 30 minutes, and then adding 0.8% of baking soda in three times, rotating for 10 minutes, 10 minutes and 60 minutes respectively.
[0013] It can be seen from the above description of the present invention that, compared with the prior art, the present invention has the following advantages:
[0014] 1. The electron pairs on the carboxyl and amino groups can form coordination bonds with the hollow hybrid orbitals of metal ions. Depending on the hybrid orbitals, coordination compounds with coordination numbers of 4, 6, or 8 can be formed. If the organic compound contains multiple active functional groups, multinuclear complexes can form when steric hindrance is low. However, the formation of multinuclear complexes rapidly increases the molecular weight of the material. When the molecular weight reaches a certain level, the complex becomes water-insoluble. Therefore, if transition metal-coordinated natural polymer materials are to be used in leather making and retanning, they must be hydrophilically modified to improve their water solubility. Since the complexes contain a large number of benzene ring structures, sulfonation can be used to graft sulfonic acid groups onto the benzene rings to improve the water solubility of the composite material.
[0015] 2. The sulfonated transition metal coordinated natural polymer material has a relatively uniform particle size and aqueous dispersibility. When prepared into a 2% aqueous solution and tested for particle size, it showed a particle size range of 1800-2500 nm, with a particle size distribution coefficient of 0.200-0.450. Skin collagen fibers are primarily 1-10 μm in size, allowing the sulfonated transition metal coordinated natural polymer material to penetrate well into the skin collagen fibers. The sulfonic acid groups pendant from the benzene rings form electrostatic interactions with amino groups on the skin collagen fibers, forming hydrogen bonds with hydroxyl and carboxyl groups. Simultaneously, the abundant carboxyl groups on the benzene rings and collagen also form electrostatic interactions with amino groups on the skin collagen fibers, forming hydrogen bonds with hydroxyl and carboxyl groups. Furthermore, the amino groups on the collagen form electrostatic interactions with carboxyl groups on the skin collagen fibers, forming hydrogen bonds with these groups. This interaction gives the sulfonated transition metal coordinated natural polymer material excellent binding and tanning properties.
[0016] 3. Sulfonated transition metal-coordinated natural polymers can improve the charge distribution of skin collagen fibers. Unretanned skin collagen fibers remain strongly anionic, but retanning with sulfonated transition metal-coordinated natural polymers increases their positive charge. This shielded negative charge effectively enhances the penetration of subsequent fillers and fatliquors into the skin collagen fibers, while reducing their surface binding. Testing of a 2% aqueous solution of sulfonated transition metal-coordinated natural polymers revealed a zeta potential ≥40 mV.
[0017] 4. The sulfonated transition metal coordinated natural polymer material has extremely strong resistance to hydrolysis. After being configured into a 10% aqueous solution, no obvious precipitation or flocculation occurs when the pH value of the solution is adjusted to a relatively strong acidic condition (i.e., pH = 2) or a relatively strong alkaline condition (i.e., pH = 10).
[0018] 5. The aromatic ring structure of the sulfonated transition metal coordinated natural polymer material has a structure similar to that of synthetic tannins, plant tannins, dyes, etc., which can promote the adsorption of synthetic tannins, plant tannins and dyes by leather collagen fibers, thereby reducing the use of dyes and improving the dyeing rate and uniformity of leather. DETAILED DESCRIPTION
[0019] Example 1:
[0020] A preparation method of a sulfonated transition metal coordinated natural polymer material retanning agent comprises the following steps:
[0021] Step 1, preparation of collagen powder: take 100 parts of blue leather scraps, add 500 parts of deionized water, mix well, add 8 parts of sodium hydroxide, react at 80°C for 4 hours, cool to room temperature, add 10 parts of calcium hydroxide, 1 part of polyaluminum chloride, and 1 part of polyacrylamide to flocculate and precipitate, filter the precipitate, take the filtrate, add sulfuric acid to adjust the pH to 7, and vacuum dry to obtain collagen powder.
[0022] Step 2, preparation of transition metal coordinated natural polymer material powder: take 100 parts of ferric chloride, 25 parts of aluminum chloride, 25 parts of cobalt chloride, 10 parts of mellitic acid, 40 parts of terephthalic acid, 65 parts of trimesic acid, 25 parts of collagen powder, and 55 parts of N,N-dimethylformamide and mix them in a hydrothermal reactor, heat to 140°C within 1 hour and keep the temperature constant for 20 hours, cool to room temperature, add 100 parts of N,N-dimethylformamide and stir for 30 minutes, filter the mixed solution, and wash with N,N-dimethylformamide, transfer the filter residue into 200 parts of N,N-dimethylformamide, stir at room temperature for 24 hours, and then filter again, wash with ethanol, and then transfer the filter residue into 200 parts of ethanol, stir at room temperature for 24 hours, filter and vacuum dry to obtain transition metal coordinated natural polymer material powder.
[0023] Step 3, improving water solubility: 100 parts of transition metal coordinated natural polymer powder and 5 parts of sodium metabisulfite are dissolved in 220 parts of water, mixed evenly, reacted at 85°C for 3 hours, and then the product is vacuum dried to obtain a sulfonated transition metal coordinated polymer material retanning agent.
[0024] Example 2:
[0025] A preparation method of a sulfonated transition metal coordinated natural polymer material retanning agent comprises the following steps:
[0026] Step 1, preparation of collagen powder: take 100 parts of blue leather scraps, add 500 parts of deionized water, mix well, add 5 parts of sodium hydroxide and 5 parts of potassium hydroxide, react at 65°C for 6 hours, cool to room temperature, add 8 parts of calcium hydroxide, 1 part of polyaluminum chloride, and 1 part of polyacrylamide to flocculate and precipitate, filter the precipitate, take the filtrate, add sulfuric acid to adjust the pH to 7.5, and vacuum dry to obtain collagen powder.
[0027] Step 2, preparation of transition metal coordinated natural polymer material powder: take 125 parts of ferric chloride, 35 parts of aluminum chloride, 12 parts of mellitic acid, 32 parts of terephthalic acid, 66 parts of trimesic acid, 20 parts of collagen powder, and 40 parts of N,N-dimethylformamide and mix them in a hydrothermal reactor, heat to 155°C within 1 hour and keep the temperature constant for 18 hours, cool to room temperature, add 100 parts of N,N-dimethylformamide and stir for 30 minutes, filter the mixed solution, and wash with N,N-dimethylformamide, transfer the filter residue into 200 parts of N,N-dimethylformamide, stir at room temperature for 24 hours, and then filter again, wash with ethanol, and then transfer the filter residue into 200 parts of ethanol, stir at room temperature for 24 hours, filter and vacuum dry to obtain transition metal coordinated natural polymer material powder.
[0028] Step 3, improving water solubility: 100 parts of transition metal coordinated natural polymer powder and 8 parts of sodium metabisulfite are dissolved in 265 parts of water, mixed evenly, reacted at 95°C for 3 hours, and then the product is vacuum dried to obtain a sulfonated transition metal coordinated polymer material retanning agent.
[0029] Example 3:
[0030] A preparation method of a sulfonated transition metal coordinated natural polymer material retanning agent comprises the following steps:
[0031] Step 1, preparation of collagen powder: take 100 parts of blue leather scraps, add 500 parts of deionized water, mix well, add 12 parts of calcium hydroxide, react at 85°C for 3 hours, cool to room temperature, add 6 parts of calcium hydroxide, 1 part of polyaluminum chloride, and 1 part of polyacrylamide to flocculate and precipitate, filter the precipitate, take the filtrate, add sulfuric acid to adjust the pH to 8, and vacuum dry to obtain collagen powder.
[0032] Step 2, preparation of transition metal coordinated natural polymer material powder: take 150 parts of ferric chloride, 50 parts of aluminum chloride, 20 parts of cobalt chloride, 15 parts of mellitic acid, 45 parts of terephthalic acid, 60 parts of trimesic acid, 15 parts of collagen powder, and 35 parts of N,N-dimethylformamide and mix them in a hydrothermal reactor, heat to 135°C within 1 hour and keep the temperature constant for 18 hours, cool to room temperature, add 120 parts of N,N-dimethylformamide and stir for 30 minutes, filter the mixed solution, and wash with N,N-dimethylformamide, transfer the filter residue into 200 parts of N,N-dimethylformamide, stir at room temperature for 24 hours, and then filter again, wash with ethanol, and then transfer the filter residue into 200 parts of ethanol, stir at room temperature for 24 hours, filter and vacuum dry to obtain transition metal coordinated natural polymer material powder.
[0033] Step 3, improving water solubility: 100 parts of transition metal coordinated natural polymer powder and 12 parts of sodium metabisulfite are dissolved in 280 parts of water, mixed evenly, reacted at 80°C for 3 hours, and then vacuum dried to obtain a sulfonated transition metal coordinated polymer material retanning agent.
[0034] The sulfonated transition metal coordinated polymer material retanning agents obtained in Examples 1, 2 and 3 were subjected to experimental testing, and the experimental data obtained are shown in Table 1 below:
[0035] Table 1
[0036] Example 1 Example 2 Example 3 Particle size / nm 1870 2151 1947 Particle size distribution coefficient 0.358 0.336 0.284 Zeta potential / mV 47.7 44.9 42.8 Acid stability Stable and no precipitation Stable and no precipitation Stable and no precipitation Alkali resistance stability Stable and no precipitation Stable and no precipitation Stable and no precipitation
[0037] Example 4:
[0038] An application of a sulfonated transition metal coordinated natural polymer material retanning agent, comprising a retanning process, a neutralization process, a filling process and a fatliquor process;
[0039] The specific steps of the retanning process are as follows: based on the weight of the wet blue leather, the drum temperature is controlled at 32°C, 50% water is added, 3% acid-resistant fatliquor (B1, Temple Chemical), 1% fatty aldehyde (PF, Zimmer Chemical) is added, the drum is rotated for 20 minutes, and 3% chrome powder (Tankrom AB, Turkey), 6% sulfonated transition metal coordinated natural polymer retanning agent, rotate for 60 minutes, then add 1% sodium formate, rotate for 30 minutes, then add 0.8% baking soda three times, rotate for 10, 10, and 60 minutes, and drain.
[0040] Neutralization process:
[0041] Based on the weight of the wet blue leather, the drum temperature was controlled at 32°C, 200% of water, 2% of neutralized tannin (A, Unitec, Italy), and 1% of sodium formate were added, and the drum was rotated for 20 minutes. 1% of baking soda and 0.5% of cyanamide carbonate were added, and the drum was rotated for 60 minutes. The leather was then washed with water and drained.
[0042] The specific steps of the filling process are as follows: based on the weight of the wet blue leather, the rotation temperature is controlled at 32°C, 50% of water is added, 3% of phosphoric acid fatliquor (SK, Unitec, Italy), 3% of amphoteric acrylic acid (TGR, Derui Chemical), and 3% of anionic acrylic resin (TP340, Zhiqi Trading) are added, and the mixture is rotated for 30 minutes. Then, 3% of melamine resin (1700, Hongfeng Polymer), 3% of dicyandiamide resin (1709, Hongfeng Polymer), and 3% of synthetic tanning agent (AN, BASF) are added and the mixture is rotated for 60 minutes. Finally, 2% of wattle bark tannin extract (FS, Unitec, Italy) and 1% of synthetic tanning agent (OS, Lanxess Chemical) are added and the mixture is rotated for 60 minutes. Finally, 0.6% of formic acid is added and the mixture is rotated for 30 minutes.
[0043] The specific steps of the fatliquor process are as follows: based on the weight of the wet blue leather, the rotation temperature is controlled at 55°C, 150% of water is added, 1% of protein filler (FB, Sichuan Desaier) is added, and the mixture is rotated for 30 minutes. Then, 3% of synthetic fatliquor (2270, Hongfeng Polymer), 3% of vegetable oil (SW, Unitec, Italy), 3% of lecithin (LC, Unitec, Italy), and 3% of neat's foot oil (OPE, Unitec, Italy) are added and the mixture is rotated for 180 minutes. Finally, 2.5% of formic acid is added in four portions and the mixture is rotated for 10, 10, 10, and 30 minutes respectively. After draining, the crust leather can be obtained.
[0044] The above is only a specific implementation of the present invention, but the design concept of the present invention is not limited to this. Any non-substantial changes to the present invention using this concept shall be deemed as an infringement of the protection scope of the present invention.
Claims
1. A method for preparing a sulfonated transition metal coordinated natural polymer material retanning agent, characterized in that: The steps include: Step 1, take 100 parts of blue leather scraps, add 500 parts of deionized water, mix well, add 8-12 parts of alkali, react at 60-90°C for 3-6 hours, cool to room temperature, add 5-10 parts of calcium hydroxide, 1 part of polyaluminum chloride, and 1 part of polyacrylamide for flocculation precipitation, filter the precipitation, take the filtrate, add sulfuric acid to adjust the pH value to 7-8, and vacuum dry to obtain collagen powder; Step 2, take 100-150 parts of ferric chloride, 25-50 parts of aluminum chloride, 0-25 parts of cobalt chloride, 10-15 parts of mellitic acid, 30-50 parts of terephthalic acid, 60-80 parts of trimesic acid, 15-30 parts of collagen powder, 35-60 parts of N, N-dimethylformamide and mix them in a hydrothermal reactor, heat to 130-160 ° C within 1 hour and keep the temperature constant for 18-24 hours, cool to room temperature, add 100-120 parts of N, N-dimethylformamide and stir for 30 minutes, filter the mixed solution, wash with N, N-dimethylformamide, transfer the filter residue into 200 parts of N, N-dimethylformamide, stir at room temperature for 24 hours, and then filter again, wash with ethanol, transfer the filter residue into 200 parts of ethanol, stir at room temperature for 24 hours, filter and vacuum dry to obtain transition metal coordinated natural polymer material powder; Step 3, take 100 parts of transition metal coordinated natural polymer powder and 5-15 parts of sodium pyrosulfite and dissolve them in 200-300 parts of water, mix them evenly, react at 80-100° C. for 3 hours, and then vacuum dry the product to obtain a sulfonated transition metal coordinated polymer material retanning agent.
2. The method for preparing a sulfonated transition metal coordinated natural polymer material retanning agent as claimed in claim 1, characterized in that: The alkali is one or more of sodium hydroxide, potassium hydroxide and calcium hydroxide.
3. The use of a sulfonated transition metal coordinated natural polymer material retanning agent as claimed in claim 1, characterized in that: At least including a retanning process; The specific steps of the retanning process are: based on the weight of the wet blue leather, the drum temperature is controlled to be 30-35°C, 50-100% of water is added, 2-4% of an acid-resistant fatliquor and 0-2% of aliphatic aldehyde are added, and the mixture is rotated for 20 minutes, 1-3% of chromium powder and 4-8% of a sulfonated transition metal coordinated natural polymer material retanning agent are added, and the mixture is rotated for 60 minutes, and then 1% of sodium formate is added, and the mixture is rotated for 30 minutes, and then 0.8% of baking soda is added in three times, and the mixture is rotated for 10 minutes, 10 minutes and 60 minutes respectively.
Citation Information
Patent Citations
Method of preparing protein polypeptide retanning agent
CN101429567A
Environment-friendly leather retanning agent based on protein hydrolysate
CN105838829A